Detection of afa and yqi in Ciprofloxacin Resistant Uropathogenic Echerichia coli - Ali Ahmed, Suaad; Flayyih, May Talib (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Antibiotic resistance has dramatically increased among UTI patients with UPEC infections. They are crucial to the pathophysiology of UTIs because UPEC invades the bladder through a variety of virulence factors. Afa adhesins are produced by human-derived Echerichia coli and have been shown to bind to the (DAF, CD55) as a receptor, while Yqi adhesin recreates a denotative role in colonization, the initial stage of pathogenesis, during infection with E.coli . E.coli isolates from 200 urine samples of credible UTI patients were detected. By employing different media, VITEK, and the biochemical identification. Susceptibility to the Ciprofloxacin antibiotic was established by using the disc diffusion approach, while the susceptibility to Ciprofloxacin and other 15 antibiotics was achieved by the VITEK 2 compact system. A tissue culture plate was used in order to analyze the adherence ability of bacteria. Genomic DNA was pulled from cells according to the protocol of ABIO pure extraction. (Quantus Fluorometer) was used to get the concentration of DNA. afa and yqi genes were detected in 22 E.coli isolates amplified by PCR using certain primers. To ascertain whether the evaluated genes were present in the bacterial isolates, PCR products were checked on a gel. Twenty-one bacterial isolates from 40,52.5% were resistant to ciprofloxacin. The highest resistance of UPEC isolates was to ampicillin (34/40, 85%) and cefazolin (33/40, 82.5%), while the lowest resistance was to amikacin and tagicycline (0/40, 0%). The results appeared to indicate that (11/25,44%) of tested UPEC were strong biofilm-forming, while the rest of the isolates (14/25,56%) were moderate biofilm-forming. The analysis of PCR products on an agarose gel revealed that out of 22 UPEC isolates, 17/22,77.27%) had the afa gene and 7/22,31.81%) had the yqi gene. The aim of this research was screening of afa and yqi genes in UPEC isolated from different UTI patients.